Effectiveness of motor interventions in infants with cerebral palsy: a systematic review. (29th March 2016) - Morgan, Catherine; Darrah, Johanna; Gordon, Andrew M; Harbourne, Regina; Spittle, Alicia; Johnson, Robert; Fetters, Linda
Abstract : Aim: To systematically review the evidence on the effectiveness of motor interventions for infants from birth to 2 years with a diagnosis of cerebral palsy or at high risk of it. Method: Relevant literature was identified by searching journal article databases (PubMed, Embase, CINAHL, Cochrane, Web of Knowledge, and PEDro). Selection criteria included infants between the ages of birth and 2 years diagnosed with, or at risk of, cerebral palsy who received early motor intervention. Results: Thirty‐four studies met the inclusion criteria, including 10 randomized controlled trials. Studies varied in quality, interventions, and participant inclusion criteria. Neurodevelopmental therapy was the most common intervention investigated either as the experimental or control assignment. The two interventions that had a moderate to large effect on motor outcomes (Cohen's effect size>0.7) had the common themes of child‐initiated movement, environment modification/enrichment, and task‐specific training. Interpretation: The published evidence for early motor intervention is limited by the lack of high‐quality trials. There is some promising evidence that early intervention incorporating child‐initiated movement (based on motor‐learning principles and task specificity), parental education, and environment modification have a positive effect on motor development. Further research is crucial. What this paper adds: Updated review of early motor intervention studies of infants with cerebral palsy found evidence of efficacy was weak. Promising approaches involve child‐initiated movement, task specificity, and environmental modification.